A single-center, prospective, observational study on maternal smoking during pregnancy in Greece: The HELENA study - George Skalis (Tobacco Prevention and Cessation, 2021)
Introduction The unequivocal association between exposure to smoke and numerous complications of pregnancy, demonstrated in the last decades, has led to a significant decrease of smoking rates in pregnancy. The aim of the present study was to determine the prevalence of maternal smoking and to elucidate factors predisposing to it among pregnant women in Athens, Greece.